Enhancing the dietary fibre in muffins with banana peel powder and evaluating its effect on physicochemical characteristics, textural quality and storage life - Paramasivam Suresh Kumar; Magesh Kumar Birundha; Subramaniyan Pushpavalli; Rajendran Arthee; Thayumanavan Shuprajhaa; Goraksha C. Wakchaure (Discover Food)
Abstract Banana peel is rich in bioactive compounds and dietary fibre, making it a valuable biomass for nutraceutical and bakery applications. This study investigates the potential of substituting refined wheat flour (RWF) with banana peel powder (BPP) at levels of 2–8% to make a nutritionally healthy muffin. The substitution with BPP significantly influenced the properties of the premix, batter, and muffins. Higher substitution levels (8%) negatively impacted the compressibility and flow properties of the premix. Light microscopy of batter revealed that different levels of RWF replacement altered cell size and numbers. SEM images showed a coarser, more irregular crumb structure in the muffins due to dietary fibre. Substitution levels of 4–8% reduced gluten content and increased dietary fibre without affecting the gluten-polysaccharide matrix, which is crucial for muffin structure and sensory attributes. A 4% addition of BPP increased total phenolics and flavonoids by 20–30%, with enhanced antioxidant activity. Storage studies demonstrated that BPP extended the muffin’s shelf life to 9 days, acted as a natural preservative compared to the 5-day shelf life for the control, while maintaining textural attributes like firmness, springiness, and chewiness. A weighed quantitative descriptive analysis (WQDA) revealed that appearance, colour, and texture were prioritized over aftertaste and bitterness in consumer preference. In conclusion, a 4% replacement of RWF with BPP resulted in muffins with improved sensory appeal and nutritional benefits, including reduced fat, lower gluten, and enhanced dietary fibre.